PEMIKIRAN SYEKH WAHBAH AL- ZUHAILY TENTANG PENYELESAIAN KONFLIK RUMAH TANGGA - Fedrik Wardiansyah (Islamic Civil Law Departement of Shari'a Faculty at Islamic State University of Sultan Maulana Hasanuddin Banten, 2023)
This paper contain an analysis of Syekh Wahbah Al-Zuhaily on solving household conflicts, today, many family couples, especially families who have just taken the household in dealing with household conflicts that begin with a disobedience attitude or not carrying out obligations carried out by one of the spouses (nusyuz), or at the stage of increasingly complicated and escalating conflicts (syiqaq), they take the divorce route in a hurry, even thought divorce is an act that Allah hates. Household couples should take the steps that need to be taken in maintaining the integrity of the household, then how are these efforts to reduce household conflict so that as much as possible there is no divorce. This paper aims to find out how efforts are made to reduce household conflicts according to Syekh Wahbah Al-Zuhaily opinion, by using the library research metod with the descriptive analysis approach, it can be concluded that according to him, there are seven stages in maintaining a household.